Chronic silencing of Drd1a-Cre+ neurons impairs dopaminergic-driven cortical activation - Messore, Luis Fernando; Vadisiute, Auguste; Edmead, Hayley; Durmaz, Aleisha; Abuelem, Mohammed; Chedotal, Flore; Hoerder-Suabedissen, Anna; Mann, Edward Oliver; Molnár, Zoltán (Frontiers in Neuroanatomy, 2025)
In the somatosensory cortex of transgenic mice, Cre-recombinase is expressed under the control of the dopamine receptor D1 (Drd1a) promoter in lower layer 6. These neurons selectively project to the higher-order thalamic nuclei and participate in the cortico-thalamo-cortical loops involved in sensory processing and stimulus representation. However, the role of dopaminergic modulation in activating this neuronal population during cortical arousal remains poorly understood. In this study, we examined the effects of D1 (SKF-81297) and D2 (Quinpirole) receptor agonists on cortical network activation. We further investigated the consequences of silencing these neurons using a Snap25 conditional knockout mouse model. We report a decrease in cellular and neuronal density in the subplate/L6b with normal development from P8 to adulthood. Conversely, the density of Drd1a-Cre+ neurons goes up in Snap25 cKO brains when comparing the same ages. Moreover, we observe that silencing of Drd1a-Cre+ neurons has no effect on microglial cells. Our results demonstrate that both D1 and D2 agonists require the Drd1a-Cre+ neurons to modulate cortical activity effectively. Our study provides new insights into the fundamental role of Drd1a-Cre+ neurons in cortical activation and sensory processing.